2023
DOI: 10.1001/jamanetworkopen.2023.32968
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tenofovir Alafenamide Fumarate for HIV Pre-Exposure Prophylaxis and Incidence of Hypertension and Initiation of Statins

Adovich S. Rivera,
Katherine J. Pak,
Matthew T. Mefford
et al.

Abstract: ImportancePre-exposure prophylaxis (PrEP) is an important tool for preventing HIV infection. However, PrEP’s impact on cardiometabolic health is understudied.ObjectiveTo examine the risk of incident hypertension and statin initiation among adult (age ≥18 years) health plan members starting PrEP with tenofovir alafenamide fumarate (TAF) compared with propensity score–matched adults taking tenofovir disoproxil fumarate (TDF).Design, Setting, and ParticipantsThis retrospective cohort study used electronic health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This study found a 14.2% increase in the risk of hypertension, alongside greater weight gain, in those who initiated DTG compared to those who initiated EFV. In addition, Rivera et al conducted a retrospective propensity‐score matched analysis of adults in California who were initiating TAF versus TDF for HIV pre‐exposure prophylaxis [ 30 ] and found that TAF use was associated with a modestly increased risk of incident hypertension. Third, an analysis of participants from the RESPOND cohort concluded that INSTIs as a class were associated with a higher incidence of hypertension than non‐nucleoside reverse transcriptase inhibitor (NNRTIs), but rates were similar in those who used protease inhibitors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found a 14.2% increase in the risk of hypertension, alongside greater weight gain, in those who initiated DTG compared to those who initiated EFV. In addition, Rivera et al conducted a retrospective propensity‐score matched analysis of adults in California who were initiating TAF versus TDF for HIV pre‐exposure prophylaxis [ 30 ] and found that TAF use was associated with a modestly increased risk of incident hypertension. Third, an analysis of participants from the RESPOND cohort concluded that INSTIs as a class were associated with a higher incidence of hypertension than non‐nucleoside reverse transcriptase inhibitor (NNRTIs), but rates were similar in those who used protease inhibitors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the primary pre-exposure prophylactic drugs for HIV-1 that have been marketed are Tenofovir Alafenamide (TAF) [ 2 , 3 ] and Dapivirine [ 4 , 5 ]. However, these drugs may have some side effects, and there are also some HIV-1-resistant strains [ 6 , 7 ]. Developing new and practical pre-exposure prophylactic drugs against HIV-1 can help humans more effectively prevent HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%